2018
DOI: 10.1089/end.2017.0477
|View full text |Cite
|
Sign up to set email alerts
|

Does Advancing Technology Improve Outcomes? Comparison of the Da Vinci Standard/S/Si to the Xi Robotic Platforms During Robotic Nephroureterectomy

Abstract: There were no significant differences between groups preoperatively. Operative time using the Xi was shorter, 184.4 vs 232.09 minutes (p = 0.0035). Other perioperative variables were similar. There was more lymphovascular invasion in group 2 (p = 0.0108), but there were higher stage tumors in group 1 (p < 0.0001). More patients underwent lymph node dissection in group 1 (p = 0.0186). Complications were similar between groups. Costs for anesthesia were less in group 1, which led to decreased total hospitalizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 13 publications
(12 reference statements)
1
16
0
Order By: Relevance
“…The reduction of the OT has influenced in turn reduction in PC because of a lower Operative Room (OR) hours. Our observation is in line with those recently report by Patel et al in urology, that revealed in a comparative study with the da Vinci Si, that the da Vinci Xi robotic nephroureterectomy reduced overall HC due to the reduction of anaesthesia and OR cost [37]. The significant reduction of the CC, was mainly due to the higher number of full robotic operations achieved with the da Vinci Xi, because it avoids the use of laparoscopic instruments and devices for the laparoscopic phase used in the hybrid technique.…”
Section: Discussionsupporting
confidence: 93%
“…The reduction of the OT has influenced in turn reduction in PC because of a lower Operative Room (OR) hours. Our observation is in line with those recently report by Patel et al in urology, that revealed in a comparative study with the da Vinci Si, that the da Vinci Xi robotic nephroureterectomy reduced overall HC due to the reduction of anaesthesia and OR cost [37]. The significant reduction of the CC, was mainly due to the higher number of full robotic operations achieved with the da Vinci Xi, because it avoids the use of laparoscopic instruments and devices for the laparoscopic phase used in the hybrid technique.…”
Section: Discussionsupporting
confidence: 93%
“…No specific exclusion criteria were used beyond case order as previously described. A 40-case cutoff was selected a priori according to literature regarding the multi-platforms comparison study [14] The first 40 consecutive RARP were performed using the da Vinci standard between December 2009 and May 2011 at the University of Udine, Italy. These were the first cases performed by the surgeon as an attending following completion of a 1-year minimally invasive urology fellowship.…”
Section: Patient Cohortmentioning
confidence: 99%
“…Despite this, the difference with the robotic one was of only 26 min which could be a consequence of the robot docking or repositioning during the procedure. In fact, a recent comparative study on RNU performed with Xi platform demonstrated OT to be shorter of about 50 min [19], as the advantage of this new platform is to smoothly perform the entire procedures without need for re-docking or patient repositioning [20]. Unfortunately, there were no other studies available to perform a sensitivity analysis on this point.…”
Section: Discussionmentioning
confidence: 99%